Quantitative Determination of Lanthanum in Lanthanum Dioxycarbonate Using Potentiometric Titration - Balaji Nagarajan; Radhakrishnan Haridharan; Gunasekar Manoharan (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
Lanthanum (LAN), a member of the lanthanide series, has a notable role in the pharmaceutical industry. The determination of LAN in Lanthanum Dioxycarbonate (La2O2CO3) holds significant importance in ensuring the quality and efficacy of pharmaceutical formulations. This research focused on the determination of lanthanum (LAN) in Lanthanum Dioxycarbonate drug substance through potentiometric titration, a vital aspect in ensuring pharmaceutical drug substance and formulation quality and efficacy. Lanthanum Dioxycarbonate, employed in treating hyperphosphatemia linked to chronic kidney disease, demands precise analytical methods for quality control. The analytical approach involves titrating Lanthanum Dioxycarbonate samples with a known concentration of ethylenediaminetetraacetic acid (EDTA) solution, with the endpoint detected potentiometrically. The study includes a rigorous analytical method validation (AMV) encompassing various parameters. The method demonstrated specificity, confirmed by the absence of blank interference and the yellow color of the solution at the endpoint with the potentiometric curve peaks indicating the absence of lanthanum. Filter compatibility study results showed that the % lanthanum content for centrifuged and filtered samples met the acceptable limits, allowing the use of 0.45 µ PVDF or 0.45 µ nylon syringe filters for regular analysis. The results obtained from centrifuged samples and both types of filtered samples met the acceptance criteria Precision was evident from consistent results, with a mean lanthanum content of 99.1% and %RSD of 0.6%. Accuracy was validated through recovery at 10%, 100%, and 150% levels, averaging 96.9% with a %RSD of 4.2%. Linearity was confirmed by a linear relationship between sample weight and titer value, with correlation coefficients exceeding 0.99 for all levels. The robustness of the study results indicated the methods’ resistance under varied conditions. Thus, the validated potentiometric titration method proved effective for determining lanthanum content in Lanthanum Dioxycarbonate drug substance, exhibiting precision, accuracy, linearity, and robustness, supporting its suitability for pharmaceutical quality control. The overall success of this analytical method validation strengthens its applicability in pharmaceutical quality control, ensuring the accurate determination of LAN content in Lanthanum Dioxycarbonate drug substance. This research addresses critical gaps in analytical methodologies for pharmaceutical drug substances and formulations containing lanthanum, contributing to the understanding of lanthanum determination.